Analisis Kemampuan Pemecahan Masalah Fisika Peserta Didik pada Materi Fluida Dinamis: Studi Pendahuluan di SMA Mekar Arum - Rifda Arifa Hanifah; Muhammad Minan Chusni (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to analyze students’ problem-solving abilities in physics regarding the topic of fluid dynamics through a preliminary study at Mekar Arum High School. The main question is how well students perform in solving physics problems. This study serves as an initial investigation to identify students’ difficulties. A descriptive method was applied involving 36 students, with data collected through observation, interviews, and diagnostic tests. The results indicate that students’ problem-solving skills remain low, particularly in the planning and evaluation stages of solution development. These findings underscore the need for a more student-centered learning approach.